Learning Abilities of Students with Intellectual Disabilities for Cooking Indonesian Traditional Food â€œOpak Bakarâ€: From Step by Step Experiment to the Analysis - Vina Pemila Apriyanti (Universitas Pendidikan Indonesia (UPI), 2023)
Children with intellectual disabilities are children who experience delays in the development of intelligence, they experience various kinds of obstacles. Therefore, children with intellectual disabilities are less able to be developed their academic learning and require development in other learning, namely in learning skills, one of which is learning the skills of making Indonesian traditional food